RISK ANALYSIS AND MANAGEMENT OF PROCUREMENT ACTIVITIES IN ELEMENTARY SCHOOL BOOK PRINTING PROJECT USING HOUSE OF RISK METHOD - Ananda Vania Arisa Putri; Rheza Aulia Ramadhan; Bambang Purwanggono Sukarsono (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Risk management is a management effort to control the company's risk operations by conducting risk analysis, risk evaluation and mitigation plan. Risk management efforts are feasible to be applied to the company's business activities including procurement activities. PT XYZ is one of the printing companies whose main demand is the printing of Elementary School Books. There is a decrease in demand that results in disruption to the company's cash flow so that a tight money policy is applied to every company's activity including procurement activities. This policy increases the risk that may occur, so risk management efforts are needed to minimize the impact that can occur. The House of Risk method is used to identify risk events and risk agents that cause them, and design mitigation measures to address those risk agents. The results showed that there were 10 risk events and 10 identified risk agents, with priority risk agents to be handled are A1 (volume and type of raw materials are incorrect) and A3 (communication interruption). There are 5 recommended mitigation measures.